Discriminant analysis of antecedents of customer retention in Malaysian retailing - Julian, Craig C.; Ahmed, Zafar U.; Che Wel, Che Aniza; Bojei, Jamil (Taylor & Francis, 2015)
This article examines the applied dimensions of relationship marketing, namely, customer service, loyalty/rewards programs, personalization, customization, and brand/store community with different customer retention levels in three retail stores in Malaysia. The relationship between customer service, loyalty/rewards programs, customization, personalization, and brand/store community with customer retention were examined via an empirical investigation of 450 loyalty/reward program members of three retail stores in Malaysia. The survey was personally administered but self-completed. All variables, namely, customer service, loyalty/rewards programs, customization, personalization, and brand/store community, were able to significantly discriminate between high and low customer retention levels. Retail managers in a developing country like Malaysia must be aware of the importance of these applied dimensions of relationship marketing (i.e., what can be done or practiced by the retailer to manage and enhance customer relationships) and how they impact customer retention levels.